Determinants of interpregnancy intervals among women in rural communities in delta state, Southern Nigeria - Rolle Remi Ahuru; Iseghohi Judith Omon; Henry Akpojubaro Efegbere (Wolters Kluwer Medknow Publications, 2022)
Aim: To guarantee safe motherhood, women are advised to adequately space their deliveries. The World Health Organization advocated for a birth interval between 3 and 5 years, yet closed birth spacing continues to be a problem in Nigeria, resulting in poor infant, child, and maternal health. This study explored the determinants of three classes of birth interval (too short, adequate, and too long) among 534 women drawn from three rural communities in Delta State, Southern Nigeria. Methods: The study is an analytical cross-sectional household survey which used a pretested structured questionnaire to elicit information from 534 women in their homes. Extracted data were analyzed with Stata version 13.0. Frequency and simple proportion were used to describe the characteristics of the women. Bivariate analysis was undertaken to show the association between birth intervals and various sociodemographic factors. Determinants of birth interval were measured by multivariate logistic regression. Statistical significance was set at P < 0.05. Results: The mean maternal age is 35.3 years (standard deviation = 7.3 years). According to the results, 74.2% (396/354) of the women reported short birth interval (<24 months), 13.7% (73/534) reported adequate birth interval, and 12.2% (65/534) reported too long birth interval. According to the multivariate logistic regression, short birth interval is significantly influenced by education, media exposure, use of contraceptive, unmet need of contraceptive, and age at marriage. Adequate birth interval is determined by education and unmet need of contraceptive. Long birth interval is predicted by education and ideal birth spacing. Conclusion: In order to encourage adequate birth spacing, education and employment opportunities should be expanded for women in the study area, and the use of modern contraceptive should be encouraged.